Quantification and Analysis of Suspended Sediments Concentration Using Mobile and Static Acoustic Doppler Current Profiler Instruments - Dwinovantyo, Angga; Manik, Henry M.; Prartono, Tri; Susilohadi, Susilohadi (Advances in Acoustics and Vibration, 2017)
The application of Acoustic Doppler Current Profiler (ADCP) can be used not only for measuring ocean currents, but also for quantifying suspended sediment concentrations (SSC) from acoustic backscatter strength based on sonar principle. Suspended sediment has long been recognized as the largest sources of sea contaminant and must be considered as one of the important parameters in water quality of seawater. This research was to determine SSC from measured acoustic backscattered intensity of static and mobile ADCP. In this study, vertically mounted 400 kHz and 750 kHz static ADCP were deployed in Lembeh Strait, North Sulawesi. A mobile ADCP 307.2 kHz was also mounted on the boat and moved to the predefined cross-section, accordingly. The linear regression analysis of echo intensity measured by ADCP and by direct measurement methods showed that ADCP is a reliable method to measure SSC with correlation coefficient (r) 0.92. Higher SSC was observed in low water compared to that in high water and near port area compared to those in observed areas. All of this analysis showed that the combination of static and mobile ADCP methods produces reasonably good spatial and temporal data of SSC.